3*6^x-1 +9*2^x+2 - 12^x - 18=0 Помогите решить!!!!
3*6^x-1 +9*2^x+2 - 12^x - 18=0
Помогите решить!!!!
Ответ(ы) на вопрос:
3x^2-12=03x^2=12x^2=12/3x^2=4x=2 2x^2+6x=02x(x+3)=02x=0 x+3=0x=0 x=-3 1.8x^2=0x^2=0x=0x^2+9=0(x+3)(x-3)=0x=+-3 7x^2-14=07x^2=14x^2=14/7x^2=2x=+-корень из 2 x^2-3x=0x(x-3)=0x=0 x-3=0 x=3 -2/3 x^2=0x^2=0x=0 6x^2+24=06x^2=-24x^2=-24/6x^2=-4 10x+2x^2=02x(5+x)=02x=0 5+x=0x=0 x=-5 15-5x^2=0-5x^2=-155x^2=15x^2=15/5x^2=3x=+- корень из 3 4.9x^2=0x^2=0x=0 6.3x-0.7x^2=063x-7x^2=07x(9-x)=07x=0 9-x=0x=0 x=9 2x^2-18=02x^2=18x^2=18/2x^2=9x=+-3 3x^2-12x=03x(x-4)=03x=0 x-4=0x=0 x=4 2.7x^2=0x^2=0x=0 x^2+16=0x=+-4 6x^2-18=06x^2=18x^2=18/6x^2=3x=+-корень из 3 x^2-5x=0x(x-5)=0x=0 x-5=0 x=5 -3/7 x^2=0x^2=0x=0 4x^2+36=04x^2=-36x^2=-9 6x-3x^2=03x(2-x)=03x=0 2-x=0x=0 x=2 12+4x^2=04x^2=-12x^2=-3 0.2x-1.8x^2=02x-18x^2=02x(1-9x)=02x=0 1-9x=0 x=0 x=1/9
Не нашли ответ?
Похожие вопросы